Anodic TiO2 nanotube layers decorated by Pd nanoparticles using ALD: An efficient electrocatalyst for methanol oxidation - Bawab, Bilal; Thalluri, Sitaramanjaneya Mouli; Rodriguez Pereira, Jhonatan; Sopha, Hanna Ingrid; Zazpe, Raul; Macák, Jan (Elsevier Science, 2022)
Herein, we report the performance of Pd nanoparticles (NPs) prepared by Atomic Layer Deposition (ALD) as a catalyst for methanol electro-oxidation. Pd NPs were decorated onto anodic TiO2 nanotube (TNT) layers as supporting material that possess a large available surface area and direct electrical contact via the underlying titanium foil. Different Pd loadings (150 - 300 - 450 - 600 ALD cycles) show different particles sizes ranging between 7 and 12 nm, as revealed by transmission electron microscopy. Coalescence dominated visibly from 450 ALD cycles, which led to a porous Pd layer all along the TNT walls rather than the growth of individual particles. Electrocatalytic performance was investigated by cyclic voltammetry (CV), where the catalytic activity increased proportional with Pd loading up to the highest values for 400 and 450 cycles, whereas a further increase in the number of ALD cycles (N-ALD) did not show any additional improvement in methanol oxidation current densities. TNT layers decorated with 400, 450 and 600 Pd ALD cycles show featureless curves suggesting complete anti-poisoning ability or possibly a proof of a direct conversion from CH3OH to CO2 (without any intermediate byproducts). The lack of an oxidation peak during the anodic scan and therefore a reduction peak during the cathodic scan, confirms Pd NPs (stabilized by TiO2) efficiently utilize OHads and chemisorbed CH3OH in a way that its CO poisoning was inhibited. As a result, the tuned high surface area TNT layers exhibited excellent performance as a supporting material for Pd NPs against formation of electrochemical poisoning species. Finally, the mechanism of the TNT layers interaction with Pd NPs, which led to the propelling methanol oxidation reaction without loss in performance over cycling is postulated.
Anodické vrstvy nanotrubic TiO2 dekorované nanočásticemi Pd pomocí ALD: Účinný elektrokatalyzátor pro oxidaci metanolu
Keywords: TiO2 nanotube layers; Pd nanoparticles; atomic layer deposition; electrocatalysis; methanol electro-oxidation; vrstvy nanotrubiček; TiO2; Pd nanočástice; depozice atomárních vrstev; elektrokatalýza; elektrooxidace metanolu